Experimental Study of the Sidewall Effect on Three-Dimensional Turbulent Wall Jet - Kumar S.; Kumar A. (My University, 2025)
An experimental study on the effect of sidewalls on the flow characteristics of a three-dimensional turbulent square wall jet is carried out at a Reynolds number of 25,000. The sidewalls are defined as the two parallel plates along the vertical jet centerline. Four different sizes of sidewall enclosure (here after referred to as ‘SWE’) are placed at the lateral positions (z) of 63:5h, 64h; 64:5h, and 65h from the vertical jet centerline plane, where h is the height of square jet. The mean characteristics of fluid flow in wall normal (y) and lateral (z) directions at different downstream locations ðx=h ¼ 0:2 - 45Þ are measured using a hotwire anemometer. The velocity measurements are also performed in the z – y lateral plane at four downstream locations ðx=h ¼ 30; 35; 40; and 45Þ. Results indicate that the mean velocity profile in lateral and wall normal directions behaves differently depending on the size of SWEs. The decay rate of the maximum mean velocity increases with decrease in size of SWEs after the downstream location ðx=h ≥ 20Þ. The decay rate of the maximum mean velocity increases about 5.6% in 140 mm SWE as compared to 200 mm SWE. It is noted that spread of the jet in wall normal and lateral directions increases with decrease in size of SWEs after the attachment of the flow stream on the sidewalls. In the far-field location of the present case, the smaller size of SWE (140 mm SWE) has 10.7% and 23.1% higher spread rate as compared to larger size of SWE (200 mm SWE) in wall-normal and lateral directions, respectively. It is also seen that the self-similar profile gets delayed in wall-normal direction as compared to lateral direction for all the cases. The wall-normal self-similar profile is obtained early with increase in the size of SWEs and it is obtained at x=h ¼30, 27, 24, and 20 for 140 mm, 160 mm, 180 mm, and 200 mm SWEs, respectively. The flow stream seems to climb the sidewall and this tendency increases with increase in size of SWEs. VC 2022 by ASME